The circular structure of Samuel Beckett’s Waiting for Godot (Journal of the College of Basic Education, 2022)
One of the distinctive features of the absurd plays, which emerged in the 1950s at the hands of some major characters like Albert Camus, Eugene Ionesco, Jean Genet and Samuel Beckett, is the unusual structure.